Stability Ball Exercises In Type 2 Diabetic Patients - SS, Subramanian; P, Venkatesan (Journal of Research in Biology, 2012)
Number of people with diabetes in India is 40.9 million and is expected to get rise to 69.9 million by 2025. Proper management can improve health of individuals with diabetes and minimize many complications that may occur among diabetic patients, along with due medications and regular physical exercises. Exercises using Stability ball were quite effective in improving the glycemic control among Type 2 diabetic patients.